MORPHOLOGICAL AND BIOCHEMICAL INDICATORS OF THE BLOOD OF FISH INFECTED WITH HELMINTHS - Kuvvatov Khusniddin Abdukhakimovich; Daminov Asadullo Suvonovich (Journals Park Publishing, 2023)
The development of the fishing industry is aimed at meeting the needs of the world's population in food products, the production of fish products that meet the requirements of environmentally friendly international standards, the analysis of literature data on morphological and biochemical changes in the body of infected fish with various infectious and non-infectious diseases, especially helminthiasis, serves to increase the quality of research conducted in this area. This article is dedicated to this area.
Keywords: Morphophysiological, physiological, biochemical, hematological, Romanovsky- Giemsa, lymphocytes, neutrophils.